Understanding the motivations of coastal residents to voluntarily purchase federal flood insurance. Issue 6 (3rd June 2017) - Brody, Samuel D.; Highfield, Wesley E.; Wilson, Morgan; Lindell, Michael K.; Blessing, Russell
Abstract : Federally-backed flood insurance is the primary mechanism by which residents in the United States (US) prepare for and recover from floods. While there is a growing literature on the general uptake of flood insurance, little work has been done to address the factors motivating residents to voluntarily buy and maintain federally-based insurance policies. We address this issue by conducting a survey of coastal residents in four localities in Texas and Florida. Based on survey responses, we quantitatively examine the factors influencing whether residents located outside of the 100-year floodplain obtain insurance policies when it is not required. Using two-sample t -tests and binary logistic regression analysis to control for multiple contextual and psychological variables, we statistically isolate the factors contributing most to the decision to purchase insurance. Our findings indicate that a resident located outside the 100-year floodplain who has voluntarily purchased federal flood insurance can be characterized, on average, as more highly educated, living in relatively expensive homes, and a long-time resident who thinks about flood hazard relatively infrequently but who, nonetheless, thinks flood insurance is relatively affordable. Unexpectedly, the physical proximity of a respondent to flood hazard areas makes little or no discernible difference in the decision to obtain flood insurance.